ANALYSIS OF THE IMPACT OF COVID IN THE SECOND YEAR ON INCOME OF WORKERS IN WEST JAVA WITH MULTINOMIAL LOGISTIC REGRESSION - Andriyati, Ani; Rohaeti, Embay; Kamila, Isti (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The COVID-19 pandemic that hit Indonesia had a huge impact on the economy. The long period of restriction of population mobility impacted the changes of people's income. West Java is the province with the most workers affected by this pandemic. The income of workers in West Java in the first five months of the pandemic decreased by 50.1%. The existence of these problems shows that an analysis of the impact of covid on changes in worker income is very necessary. This study aims to determine the factors that have a significant effect on changes in workers' income in West Java. Based on the results of the multinomial logistic model suitability test, it was found that there was no difference in the model between the observed results and the predicted results for male workers, therefore the model could be used. In the second year of the covid pandemic, the opportunity for a person's income to decrease in West Java is still very high, at 0.9891. The factors with the highest opportunities that affect income changes in the reduced category are self-employed employment status, changes in work hours, the implementations of WFH, and workers working at terminal/station/airport locations.